Crossfire over the classics: Revisiting fifty years of polemics on the category of totalitarianism (1960-2010) - Varajidás, Henrique (2021)
By aiming beyond the mere historical contextualization of the accumulated trove of reflections on totalitarianism, this article intends to reorder and reinterpret them using a heuristic grid of an eminently theoretical nature. We aim to explain how and with what justification the authors who most intensely focused on the subject in the 1940s and 1950s went, between the 1960s and the beginning of the present century, from nuclear to neglected within the area of totalitarianism studies. As the key to explaining this trajectory, we pinpoint the nature of the category’s neo-apologists’ reaction to three major criticisms formulated against it in the 1960s and 1970s.